1996
DOI: 10.1021/ic951462u
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for the Homolytic Cleavage of Alkyl Hydroperoxides by the Manganese(III) Dimer MnIII2(2-OHsalpn)2

Abstract: The oxidation of MnIII 2(2-OHsalpn)2, 1 (2-OHsalpn = 1,3-bis(salicylideneamino)-2-propanol), with tert-butyl hydroperoxide was studied in organic media. A one-electron reaction occurs resulting in initial formation of the oxidized MnIIIMnIV(2-OHsalpn)2OH species 2 and a tert-butoxy radical. The MnIIIMnIV(2-OHsalpn)2OH complex can be readily protonated to yield MnIIIMnIV(2-OHsalpn)2 +. Upon addition of excess tert-butyl hydroperoxide, singlet dioxygen is evolved in an exothermic reaction indicative of radical-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 63 publications
6
55
0
Order By: Relevance
“…As an example, protonation or methylation of the oxo-bridge destroyed the catalase activity of these compounds. Possibly most important, these were the first manganese oxo bridged molecules for which homolytic bond dissociation energies were reported [104]. These data demonstrated that the energetics of water oxidation were precisely tuned to both the proton and the electron and that proton coupled electron transfer (PCET) or H-atom abstraction were likely to be involved in water oxidation chemistry [9,89,143].…”
Section: Mn-μ-o 2 -Mnmentioning
confidence: 87%
See 1 more Smart Citation
“…As an example, protonation or methylation of the oxo-bridge destroyed the catalase activity of these compounds. Possibly most important, these were the first manganese oxo bridged molecules for which homolytic bond dissociation energies were reported [104]. These data demonstrated that the energetics of water oxidation were precisely tuned to both the proton and the electron and that proton coupled electron transfer (PCET) or H-atom abstraction were likely to be involved in water oxidation chemistry [9,89,143].…”
Section: Mn-μ-o 2 -Mnmentioning
confidence: 87%
“…They showed the first 2.7Å Mn-Mn separations [99], the distance that forms the structural hallmark of the catalytic center and served as the basis for testing the famous "Dimer of dimers" structural model for the enzyme [99][100][101]. In addition, studies of the reactivity to form and destroy the dimers, along with perturbations of the properties upon protonation of these oxo bridges has proved critical to the viability of more recent water oxidation proposals [102][103][104].…”
Section: Mn-μ-o 2 -Mnmentioning
confidence: 99%
“…For clarity, only the terminal Mn III ions of complex 1 are considered. We propose that after the coordination of the tBuOOH oxidant to the Mn III centre, the homolytic breakage of the O-O bond [79] would lead to the release of the radical tBuO…”
Section: Formation Of the Mn IV -Hydroxo Entitiesmentioning
confidence: 99%
“…No compounds are available containing Mn and Ca, which are bridged by mono-µ-oxo or carboxylate bridges. Even though a great many Mn compounds, relevant to the OEC, have been published, only a few of these of compounds have been studied by XANES 35,[186][187][188][189][190][191][192][193][194][195][196] or Mn Kβ XES. 46,[197][198][199] In fact, some of the compounds involved are manganese salts, such as Mn II Cl 2 , or oxides, such as Mn 2 O 3 , which are less relevant to the OEC.…”
Section: -21mentioning
confidence: 99%
“…46,[197][198][199] In fact, some of the compounds involved are manganese salts, such as Mn II Cl 2 , or oxides, such as Mn 2 O 3 , which are less relevant to the OEC. 38,190,193,194,198 The focus of these studies is on either the influence of an oxidation-state change 191,192,196,197 or a structural change [186][187][188]195 …”
Section: -21mentioning
confidence: 99%